The kindness pact : 8 promises to make you feel good about who you are and the life you live. - Bertolucci, Domonique (Hardie Grang Books, 2021)
The Kindness Pact is happiness expert Domonique Bertolucci's answer to feeling good about who you are and the life you live. The Kindness Pact introduces us to the Eight Promises: commitments to make for lasting happiness. Each chapter explores one of the Eight Promises, using inspiring stories of personal change to show us how to be as kind to ourselves as we are to our loved ones. When we keep the Pact, we build our confidence, nurture our self-esteem and have more energy to do what we want to do and be who we want to be. With its new illustrated cover, The Kindness Pact is a beautiful gift that keeps giving.